Kedaluwarsa dan Grasi Sebagai Dasar Hapusnya Kewenangan Menjalankan Pidana, Perlukah Diatur Kembali dalam RUU KUHP? (Expiration and Clemency as a Basis for Abolishing Punishment, Does it Need to Be Rearranged in the Criminal Code Bill?) - Lidya Suryani Widayati (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
Regulations regarding the abolition of the authority to carry out criminal prosecution, namely granting clemency and determining expiration, cause a prosecutor to be unable to execute a court decision against a convicted person. In comparison, the state’s right to impose and execute the convicted person refers to the legitimacy or justification of punishment. Using a normative juridical approach and secondary data, this paper examines the granting of clemency and expiring arrangements to carry out sentences from the perspective of punishment, especially from the purpose of punishment. The results of the study are to determine whether the granting of clemency and the determination of expiration can be rearranged in the Criminal Code Bill. This study aims to analyze the policy of granting clemency and the determination of expiration of carrying out crimes from the perspective of punishment, especially from the purpose of punishment. Referring to the objectives of punishment as formulated in the Criminal Code Bill, there is an inconsistency between the the punishment objectives to be achieved. It is different from the abolition of carrying out a crime because of clemency by the president. Granting clemency is in line with the purpose of punishment, namely to restore balance and create peace in society. With regard to the purpose of punishment as formulated in the Criminal Code Bill, in the discussion of the Bill, the House of Representatives of the Republic of Indonesia (DPR RI) and the government should be able to review the expiration arrangement so that it does not become a basis for abolishing criminal prosecution. AbstrakPengaturan mengenai hapusnya kewenangan menjalankan pidana, yaitu pemberian grasi dan penentuan kedaluwarsa, menyebabkan seorang jaksa tidak dapat mengeksekusi putusan pengadilan terhadap terpidana. Sedangkan hak negara untuk menjatuhkan dan mengeksekusi terpidana mengacu pada legitimasi atau dasar pembenaran dari pidana. Melalui pendekatan yuridis normatif dan dengan menggunakan data sekunder, tulisan ini mengkaji kebijakan pemberian grasi dan penentuan kedaluwarsa menjalankan pidana dari perspektif pemidanaan terutama dari tujuan pemidanaan. Hasil kajian ini untuk menentukan apakah pemberian grasi dan penentuan kedaluwarsa tersebut perlu diatur kembali dalam Rancangan Undang-Undang tentang Kitab Undang-Undang Hukum Pidana (RUU KUHP). Apabila mengacu pada tujuan pemidanaan sebagaimana dirumuskan dalam RUU KUHP kebijakan pengaturan kedaluwarsa justru tidak sejalan dengan tujuan pemidanaan yang hendak dicapai. Berbeda dengan hapusnya kewenangan menjalankan pidana karena adanya pemberian grasi oleh presiden. Pemberian grasi sejalan dengan tujuan pemidanaan yaitu untuk memulihkan keseimbangan dan mendatangkan rasa damai dalam masyarakat. Terkait dengan tujuan pemidanaan sebagaimana yang telah dirumuskan dalam RUU KUHP maka dalam pembahasan RUU tersebut, Dewan Perwakilan Rakyat Republik Indonesia (DPR RI) dan Pemerintah hendaknya dapat mengkaji kembali pengaturan kedaluwarsa agar tidak menjadi dasar hapusnya kewenangan menjalankan pidana.